PENERAPAN PEMBELAJARAN BERBASIS LITERASI UNTUK MENINGKATKAN MINAT BACA DI SEKOLAH DASAR - Fitrah, Fitrah (Jurnal Sultra Elementary School, 2023)
Reading interest among elementary school students is often a challenge faced by educators in various regions. Literacy-based learning can be one solution to increase students' reading interest. This journal discusses the implementation of literacy-based learning in elementary schools with the aim of increasing students' reading interest. This literature study covers various learning approaches, media use, and the role of teachers in creating an environment that supports a culture of literacy in schools. The results of the study indicate that the implementation of literacy-based learning strategies that actively involve students in reading activities can significantly increase their reading interest.